2007
DOI: 10.1016/j.cell.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Rotation and Catalysis in F1-ATPase Revealed by Single-Molecule Imaging and Manipulation

Abstract: F(1)-ATPase is a rotary molecular motor that proceeds in 120 degrees steps, each driven by ATP hydrolysis. How the chemical reactions that occur in three catalytic sites are coupled to mechanical rotation is the central question. Here, we show by high-speed imaging of rotation in single molecules of F(1) that phosphate release drives the last 40 degrees of the 120 degrees step, and that the 40 degrees rotation accompanies reduction of the affinity for phosphate. We also show, by single-molecule imaging of a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
491
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(536 citation statements)
references
References 29 publications
33
491
8
Order By: Relevance
“…Such modifications may add or remove barriers to the rotation not present in the native system. Consequently, the reported rotation rates vary greatly in such studies, depending on the gene-engineered construct and the details of the artificial environment of the enzyme (Panke and Rumberg 1997;Masaike et al 2000;Itoh et al 2004;Imamura et al 2005;Adachi et al 2007;Takeda et al 2009). Such studies are not possible on a native enzyme in a native membrane, but since the ATP/rotation stoichiometry is known, one could assay the inorganic phosphate liberated from ATP hydrolysis by V-ATPase in unit time and relate it to the concentration of V-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…Such modifications may add or remove barriers to the rotation not present in the native system. Consequently, the reported rotation rates vary greatly in such studies, depending on the gene-engineered construct and the details of the artificial environment of the enzyme (Panke and Rumberg 1997;Masaike et al 2000;Itoh et al 2004;Imamura et al 2005;Adachi et al 2007;Takeda et al 2009). Such studies are not possible on a native enzyme in a native membrane, but since the ATP/rotation stoichiometry is known, one could assay the inorganic phosphate liberated from ATP hydrolysis by V-ATPase in unit time and relate it to the concentration of V-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach in the case of mammalian (human and bovine) F 1 -ATPase Walker and coworkers (Bason et al 2014) found three such states about 65°, 25°and 30°apart. A somewhat similar 80°, 10°and 30°division of the 120°for the dwells of the thermophilic Bacillus ATPase studied in current single-molecule experiments has been suggested (Adachi et al 2007) based on a mutant that retards the rate and permits an improved time-resolution. Kinosita and coworkers (Adachi et al 2007) suggested that the combined 10°and 30°substeps give rise to the 40°substep resolved in previous single-molecule experiments (Nishizaka et al 2004) and associated with hydrolysis and Pi release in a different subunit (Watanabe & Noji, 2014;Watanabe et al 2010).…”
Section: There Is a Concerted Kinetics Of Binding Hydrolysis And Relmentioning
confidence: 80%
“…A somewhat similar 80°, 10°and 30°division of the 120°for the dwells of the thermophilic Bacillus ATPase studied in current single-molecule experiments has been suggested (Adachi et al 2007) based on a mutant that retards the rate and permits an improved time-resolution. Kinosita and coworkers (Adachi et al 2007) suggested that the combined 10°and 30°substeps give rise to the 40°substep resolved in previous single-molecule experiments (Nishizaka et al 2004) and associated with hydrolysis and Pi release in a different subunit (Watanabe & Noji, 2014;Watanabe et al 2010). The 10°is presumably the hydrolysis step, a similar small 15°hydrolysis step is supported by a very approximate independent analysis (Volkán- Kacsó & Marcus, 2017b), but the latter can be improved when more accurate kinetic data in the stalling experiments become available.…”
Section: There Is a Concerted Kinetics Of Binding Hydrolysis And Relmentioning
confidence: 80%
See 2 more Smart Citations